2017
DOI: 10.20964/2017.06.67
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of CO2 Reduction on Nano Silver Cathode in Ionic Liquid BMIMBF4: Synthesis of Dimethylcarbonate

Abstract: Nano silver particles deposited on conductive glass was prepared by cyclic voltammogram. This obtained electrode was used to catalyze electroreduction of carbon dioxide for synthesize dimethylcarbonate. Results show that the process of electrochemical reduction of CO 2 on nano silver particles electrode in 1-butyl-3-methylimidazoliumtetrafluoborate (BMIMBF 4 ), is step by step, which is proved by two reduction peaks at -1.8 V and -2.2 V (vs. Ag). Under mild conditions, electrolyses experiments were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Specifically, pair peaks at 159.3 and 164.6 eV verified the existence of Bi 3+ in the BiOCl nanosheet (Fig. 1 b, red curve) [ 3 ]. Similar peaks were found in the XPS spectrum of the commercial Bi powder, as indicated by peaks at 158.7 and 164.0 eV, which are slightly deviated from those in BiOCl nanosheet due to inevitable oxidation to air exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, pair peaks at 159.3 and 164.6 eV verified the existence of Bi 3+ in the BiOCl nanosheet (Fig. 1 b, red curve) [ 3 ]. Similar peaks were found in the XPS spectrum of the commercial Bi powder, as indicated by peaks at 158.7 and 164.0 eV, which are slightly deviated from those in BiOCl nanosheet due to inevitable oxidation to air exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The excessive exploitation and utilization of fossil fuels trigger serious environmental issues and energy crises which have aroused widespread concerns [1]. Electrochemical CO 2 reduction reaction (CO 2 RR), powered by intermittent renewable energy resources (such as solar, wind, or tide energy) meanwhile producing valuable liquid fuels or chemicals, forms a carbon-neutral cycle [2][3][4][5][6]. A recent technical and economic analysis of CO 2 RR revealed that the high market competitiveness of formate as the most economically viable product with the advantages of non-toxicity, safety, and non-flammability, which can be used directly in formic acid fuel cells or as hydrogen storage carrier [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The severe adverse effects of global warming resulting from excessive carbon dioxide (CO 2 ) emission arouses the need for urgent research into CO 2 reduction. CO 2 conversion to valued-added chemicals or fuels has gained enormous research interest as a game-changing technology for sustainable development [ 1 , 2 , 3 , 4 , 5 ]. Artificial photosynthesis, which mimics natural photosynthesis using renewable solar energy and water to convert CO 2 to manageable chemicals while leaving oxygen as a by-product, has been considered as one of the most green and sustainable technologies [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the years following these two reports, only a few articles have been published, most of which deal with the incorporation of CO 2 into organic molecules. The reactions identified include aromatic ketone electrocarboxylation, electrochemical CO 2 cycloaddition to epoxides, ,, electrocarboxylation of acyl halides, electrosynthesis of dialkyl carbonates from alcohols, CO 2 , and alkyl iodides, electrosynthesis of carbamates using amines, , electrocarboxylation of alkyl or aryl halides, and olefin electrocarboxylation . In several cases, the organic electrosynthesis performed with IL electrolytes does not involve the direct reduction of CO 2 to the anion radical.…”
Section: Electrocatalysismentioning
confidence: 99%